THE ANALYSIS NETWORK FORENSICS USING HONEYPOT ON PUBLIC CLOUD COMPUTING SERVICE NETWORK - Winda Andrini Wulandari (Fakultas Teknik Universitas Lambung Mangkurat, 2018)
This research presents visualization in dashboard using AWN campus honeypot log data connected to IHP (Kemkominfo) Jakarta on public cloud computing service network to categorize time stamp in data. Package attack data is divided into three categories namely morning, noon, and night based on Time Western Indonesia (WIB). DDoS attacks attacked several ports 21, 80, 135, and 445. K -means clustering method is implemented in this research to get categorization result of time of effective attack to know DDoS attack attack and cyber profilling which is expected to help monitoring process of anticipation of vulnerability cloud network of ddos / cyber crime attacks. The results of this study indicate that the method used to obtain results in accordance with the objectives.